Critical peripheral ischemia precipitated by severe episode of Raynaud's phenomenon in a patient with aPL-positive systemic lupus erythematosus, upon high titer anti-RNP seroconversion. (March 2015) - Levy, O; Maslakov, I; Vosco, S; Markov, A; Amit-Vazina, M; Tishler, M
A 35-year-old female with long standing aPL-positive lupus without history of thromboembolic events, who has developed critical peripheral ischemia (CPI) is described. An episode of severe Raynaud's phenomenon rapidly progressed to an extensive digit-threatening ischemia, involving bilateral hands and feet. She was successfully treated with corticosteroids, anticoagulation, iloprost, sildenafil, and nifedipine. Her serological studies were remarkable for the emergence of high titer anti-RNP seroconversion and an increase in aPL titer, suggesting that these autoantibodies played a role in the pathogenesis of CPI. It is important to note that such observation should herald this potentially devastating complication of systemic lupus erythematosus.